PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PERUSAHAAN (STUDI KASUS CV. SUKSES ABADI) - Fauziah Nur Purwaningsih; Mekar Meilisa Amalia (Worksheet : Jurnal Akuntansi, 2021)
A very important part of the company's operational management that reflects thecondition of the company's performance is internal control. Effective internalcontrol can help companies safeguard company assets, ensuring the availability ofaccurate financial reports. To determine the internal control system affectscompany performance at CV. Sukses Abadi is the goal of this study. Quantitativeresearch is a type of this research. The saturated sample is a sampling techniquefor this study. The analysis method used in this research is descriptive analysismethod and simple linear regression analysis were the tests carried out includevalidity, reliability, classical assumption tests (normality test, heteroscedasticitytest), partial test (t-test) and to determine the relationship between each variableusing correlation coefficient analysis. The results of the study explained that thecorrelation value (R) was 0.561. From the output, the coefficient of determination(R Square) is 0.330, which means that the influence of the independent variable(internal control system) on the dependent variable (company performance) is33.00% and the rest is 67.00%. Furthermore, the results of research on theinfluence of internal control systems on company performance at CV Sukses Abadican conclude that there is a significant and positive influence of internal control oncompany performance at CV. Sukses Abadi in Deli Serdang Regency which isshown based on the results of the t value of 2.054> t table of 2.048 and a probabilityvalue of 0.049 <0.05 means that the better internal control carried out by themanagement of CV. Sukses Abadi, the higher the company's performance